2011
DOI: 10.1186/1756-0500-4-218
|View full text |Cite|
|
Sign up to set email alerts
|

Spermatocytic seminoma at the National Institute of Oncology in Morocco

Abstract: BackgroundSpermatocytic seminoma (SS) is a distinct testicular germ cell tumor, representing less than 1% of testicular cancers. The clinical features that distinguish ss from classical seminoma are an older age at presentation and a reduced propensity to metastasize. The aim of our work is to underline the epidemiological, clinical, histological, therapeutical and prognostic features of this tumor.FindingsA retrospective analysis of patients referred to the national institute of oncology with seminoma, identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Positive c-Kit (also known as CD117) staining is controversial. While Raiss and colleagues showed four cases of SS were all negative for CD117 [11], Decaussin and colleagues found c-Kit was expressed in 100% of seven SS cases [26]. C-Kit positivity was also shown by Dundr and colleagues [6] and Narang and colleagues [21].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Positive c-Kit (also known as CD117) staining is controversial. While Raiss and colleagues showed four cases of SS were all negative for CD117 [11], Decaussin and colleagues found c-Kit was expressed in 100% of seven SS cases [26]. C-Kit positivity was also shown by Dundr and colleagues [6] and Narang and colleagues [21].…”
Section: Discussionmentioning
confidence: 98%
“…An extensive literature review revealed that the incidence of SS varies between 1.1 and 12% of all seminomas [4,10] and 1% of all testicular neoplasms [11]. The incidence of bilaterality, either synchronous or metachronous, is nearly 10% of cases [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III GCTs, the spermatocytic tumor are detected in the 5th-6th decade of life and are a rare GCT (<1% of testicular tumors) (Looijenga & Oosterhuis 1999, Oosterhuis & Looijenga 2005, Raiss et al 2011 (Fig. 1A).…”
Section: Germ Cell Malignanciesmentioning
confidence: 99%
“…Following the publication of our article [1], we realised that we did not give correct attribution to our previous publication [2]:…”
mentioning
confidence: 99%